SERVICES OFFERED BY THE OTTOMAN-LIBRARIES - 1400-1839 - (:unkn) unknown (K G SAUR VERLAG KG, 1993)
In previous articles we discussed certain developments in Ottoman libraries focusing on their collections and catalogues.1 In this article we will examine, from the evidence available, the services which the Ottoman libraries offered their readers, dwelling on the hours of opening, the activities carried on within the library and the policy towards lending books.